Pengaruh gaya mengajar guru terhadap minat belajar siswa SD/MI - Didit Darmawan; Denis Nurista Sari (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2026)
Teaching methods play a crucial role in fostering students’ leaerning interest at Madrasah Ibtidaiyah and Elementary Schools, particularly because at this stage, the learning experience is heavily influenced by how teachers manage the learning process. Based on this context, this study aims to examine the relationship between teachers’ teaching styles and students’ learning interest based on various findings from previous research. This study was conducted through a literature review using a qualitative-descriptive approach. Data were obtained from a search of relevant scientific sources, such as journal articles and academic publications related to teachers’ teaching styles and students’ learning interest at SD/MI. Subsequently, the data were analyzed descriptively to identify patterns in the findings, the consistency of research results, and the factors influencing the relationship between these two variables. The findings of this study indicate that varied, communicative, and interactive teaching methods, supported by the use of engaging educational media, have a positive and noteworthy impact on enhancing students’ learning interest. Conversely, teacher-centered and repetitive teaching methods generally reduce students’ attention and enthusiasm for learning. Students’ enthusiasm for participating in the learning process, their learning interest, and their level of engagement can be enhanced through diverse and interactive teaching styles tailored to students’ characteristics. On the other hand, teaching approaches that are boring and fail to engage students tend to diminish their learning interest. Teachers play a crucial role in efforts to strengthen the educational process, serving both as providers of instructional content and as role models who shape students’ attitudes and motivate them to be enthusiastic about learning. The results of this study confirm that innovations applied to learning styles will help increase learning interest, student engagement, and improve the overall quality of the learning process. Metode pengajaran memiliki peranan penting dalam menumbuhkan minat belajar siswa di Madrasah Ibtidaiyah (MI) dan Sekolah Dasar (SD), terutama karena pada tahap ini pengalaman belajar sangat dipengaruhi oleh cara guru mengelola pembelajaran. Berangkat dari kondisi tersebut, penelitian ini bertujuan mengkaji hubungan gaya mengajar guru dengan minat belajar siswa berdasarkan berbagai temuan penelitian terdahulu. Kajian ini dilakukan melalui tinjauan literatur dengan pendekatan kualitatif-deskriptif. Data diperoleh dari penelusuran sumber ilmiah yang relevan, seperti artikel jurnal dan publikasi akademik terkait gaya mengajar guru dan minat belajar siswa SD/MI. Selanjutnya, data dianalisis secara deskriptif untuk menelusuri pola temuan, kesesuaian hasil penelitian, serta faktor-faktor yang memengaruhi hubungan kedua variabel tersebut. Temuan studi ini menunjukkan bahwa metode pengajaran guru yang variatif, komunikatif, interaktif, dan didukung penggunaan media pendidikan yang menarik memiliki dampak yang positif dan patut diperhatikan pada peningkatan minat belajar siswa. Sebaliknya, metode pendidikan yang berpusat pada guru dan bersifat repetitif umumnya mengurangi perhatian serta antusiasme siswa dalam belajar. Semangat siswa untuk berpartisipasi dalam proses belajar, minat siswa dalam belajar, dan tingkat keterlibatan mereka dapat ditingkatkan melalui gaya pengajaran guru yang beragam dan interaktif yang disesuaikan dengan karakteristik siswa. Di sisi lain, pendekatan pengajaran yang membosankan dan tidak melibatkan siswa akan cenderung menurunkan ketertarikan siswa dalam belajar. Guru memegang peranan penting di tengah upaya memperkuat proses pendidikan, yakni sebagai penyedia materi yang diajarkan sekaligus sebagai teladan yang membentuk sikap serta memotivasi siswa untuk semangat dalam belajar. Hasil penelitian ini menegaskan bahwa inovasi yang diterapkan dalam gaya belajar akan membantu peningkatan minat belajar, keterlibatan siswa, dan menambah mutu proses belajar secara keseluruhan.